NEONATAL NECROTIZING ENTEROCOLITIS: CLINICAL DATA AND TREATMENT POSSIBILITIES - Elena Hanganu; Maria Stamatin; S.G. Aprodu; Mihaela Moscalu; Simona Gavrilescu (Amaltea Medical Publishing House, 2014)
Objectives. The aim of this paper is to identify the correlations between the clinical evolution of the neonates with necrotizing enterocolitis (NEC) and the stage of disease, associated risk factors and the type of treatment used. Material and methods. A 6 years retrospective study was performed based on reviewing the casuistry of the Regional Centre of Neonatal Intensive Care Unit (NICU) "Cuza Voda" and 205 cases of necrotizing enterocolitis were identifi ed from a total number of 6183 neonates admitted there. Patients were divided in to study groups based on the gestational age (GA) and birth weight (BW). The analysis protocol was realized based on a working sheet that included the epidemiological data of the patients, the risk factors, type of nutrition, age at diagnosis, stage of disease according to Bell classifi cation, type of treatment (medical, surgical or combined), complications and the general evolution. The statistical data processing was performed in SPSS Statistics 20 program. Results. NEC had a frequency of 3.3% is the study group and was diagnosed in premature newborns in 75.6% of cases. The mean GA for the study group was 33 weeks. The mean BW was 1896 g with 43% of the cases in very low birth weight (VLBW) group and 31.2% in low birth weight (LBW) group. The percentage incidence of the risk factors was as follows: persistence of ductusarteriossus 19.5%, perinatal asphyxia 13.7% and respiratory distress 100% of cases. 75.5% were treated and discharged from NICU, 16.6% were transferred to Pediatric Surgery Department "Sf. Maria" and 3.9% died in NICU. From the 34 cases transferred19 cases were surgically treated: 8 cases with peritoneal drainage (PD), 8 cases with primary laparotomy (LAP) and 3 cases with PD and LAP. The survival rate in this group was 2.4% and for the medically treated group was 4.9%. Conclusions. Prematurity is statistically correlated with encountering advanced stages of enterocolitis at the time of diagnosis. The option for surgical treatment (peritoneal drainage or laparotomy) does not infl uence the results and early enteral feeding with formula is the most important risk factor for NEC followed by age of gestation and very low birth weight.